COMMERCIALIZATION OF MSME DIGITALIZATION INCUBATION WITH BUSINESS DEVELOPMENT OF PROFIT SHARING AND EQUITY FUNDING MODELS - Dwi Wulandari; Putra Hilmi Prayitno; Andi Basuki; Abdul Rahman Prasetyo; Fikri Aulia; Ari Gunawan; Afis Baghiz Syafruddin (Dharmas Education Journal (DE_Journal), 2024)
MSMEs in Indonesia play a vital role in the economy, contributing more than 60% to GDP and absorbing 97% of the workforce. Digitalization provides new opportunities for MSMEs to increase competitiveness and diversify income sources, but challenges remain, such as low digital literacy, access to technology, and lack of training. This study aims to develop and determine the effectiveness of MSME digitalization incubation that combines profit-sharing and equity funding business models. The research method used is the business model canvas method with a quantitative and qualitative approach. The study results show that digitalization incubation programs significantly positively impact the growth of MSMEs, with 45% of respondents stating that digitalization is essential in improving business performance. However, only 30% of MSMEs understand the concept of equity funding well, indicating the need to improve financial literacy. In addition, the study found that trust in the profit-sharing model was higher than equity funding, with 40% and 35%, respectively. The implication of this study is the need to increase MSMEs' understanding and accessibility to digitalization-based business models through more comprehensive incubation programs, as well as the development of policies that support the strengthening of financial literacy among MSME actor.